Corporate governance and IPO underpricing in a cross‐national sample: A multilevel knowledge‐based view - Judge, William Q.; Witt, Michael A.; Zattoni, Alessandro; Talaulicar, Till; Chen, Jean Jinghan; Lewellyn, Krista; Hu, Helen Wei; Shukla, Dhirendra; Bell (Robert), R. Greg; Gabrielsson, Jonas; Lopez, Felix; Yamak, Sibel; et al. (Strategic Management Journal, 2015)
Prior studies of IPO underpricing, mostly using agency theory and single‐country samples, have generally fallen short. In this study, we employ the knowledge‐based view ( KBV ) to explore underpricing across 17 countries. We find that agency indicators are insignificant predictors, board of director knowledge limits underpricing, and external knowledge both substitutes for and complements internal board knowledge. This third finding suggests that future KBV studies should consider how internal and external knowledge states interact with each other. Our study offers new insights into the antecedents of underpricing and extends our understanding of comparative governance and the KBV of the firm . Copyright © 2014 John Wiley & Sons, Ltd.